2001
DOI: 10.1089/105072501300176462
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-Induced Hypothyroidism

Abstract: Iodine is an essential element for thyroid hormone synthesis. The thyroid gland has the capacity and holds the machinery to handle the iodine efficiently when the availability of iodine becomes scarce, as well as when iodine is available in excessive quantities. The latter situation is handled by the thyroid by acutely inhibiting the organification of iodine, the so-called acute Wolff-Chaikoff effect, by a mechanism not well understood 52 years after the original description. It is proposed that iodopeptide(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
251
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(260 citation statements)
references
References 72 publications
3
251
1
5
Order By: Relevance
“…Vitale et al (30) and our previous experimental studies revealed that high iodine intake damages endogenous thyroid peroxidase and induces apoptosis in these cells through a mechanism that involves the generation of free radicals (30)(31)(32), but whether the iodine-induced apoptosis contributes to chronic iodine-induced hypothyroidism is unknown. It has been reported that iodine-induced hypothyroidism usually resolves quickly after iodine withdrawal, but if the administration of iodide continues, overt or subclinical hypothyroidism will persist (33). Even though the symptoms of subclinical hypothyroidism are less, complications can be severe.…”
Section: Discussionmentioning
confidence: 99%
“…Vitale et al (30) and our previous experimental studies revealed that high iodine intake damages endogenous thyroid peroxidase and induces apoptosis in these cells through a mechanism that involves the generation of free radicals (30)(31)(32), but whether the iodine-induced apoptosis contributes to chronic iodine-induced hypothyroidism is unknown. It has been reported that iodine-induced hypothyroidism usually resolves quickly after iodine withdrawal, but if the administration of iodide continues, overt or subclinical hypothyroidism will persist (33). Even though the symptoms of subclinical hypothyroidism are less, complications can be severe.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind an iodine-induced increase in the incidence of hypothyroidism is unknown, but several mechanisms could be involved. Iodine has been associated with thyroid autoimmunity (43), and it has a number of autoregulatory inhibitory effects on thyroid hormone production and secretion (44). Moreover, excess iodine may lead to apoptosis of thyroid follicular cells as studied in in vitro systems (45).…”
Section: Iodine Intake and The Incidence Of Overt Hyper-and Hypothyromentioning
confidence: 99%
“…The effect of the consumption of additional iodine is also dependent on the initial status of the population. In populations that are mildly deficient or replete, increases in dietary iodine may induce hypothyroidism, while in populations that were previously severely deficient, increased dietary iodine is associated with hyperthyroidism 4,5 . Iodine-induced hyperthyroidism (IIH) is a serious condition that may in extreme cases lead to death, usually from heart-associated causes 6 .…”
mentioning
confidence: 99%